The Neutralization and Denial of Sexual Violence in College Party Subcultures. Issue 12 (1st December 2016) - Boyle, Kaitlin M.; Walker, Lisa Slattery
ABSTRACT: Heavy drinking and sexual assault are prevalent among college students who attend parties hosted by fraternities and athletic teams, and accusations often produce victim blaming and disbelief. We provide a symbolic interactionist explanation of how subculturally held sentiments shape students' perceptions. We find that fraternity or athletic team party attendees (but not those who drink in other settings) are more likely than abstainers to hold stereotypical definitions of rape, rate sexual assault as less likely, and are less likely to acknowledge an assault as rape. This study offers a potential mechanism—meanings transmitted and sustained within subcultures—for explaining the denial of rape among students who attend parties hosted by fraternities or athletic teams.